The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jnp.12298
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity between the hippocampus and cortical/subcortical area relates to cognitive impairment in schizophrenia but not in mood disorders

Abstract: Cognitive impairment in schizophrenia and other psychiatric disorders is a challenge to be overcome in order to maintain patients' quality of life and social function. The neurological pathogenesis of cognitive impairment requires further elucidation. In general, the hippocampus interacts between the cortical and subcortical areas for information processing and consolidation and has an important role in memory. We examined the relationship between structural connectivity of the hippocampus and cortical/subcort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…At the within-network level, we discovered decreased intrinsic FC in the cortico-hippocampal network, including the AT system, the PM system, and the anterior and posterior hippocampus, which is partially consistent with prior reports for schizophrenia (Benetti et al, 2009;Belujon et al, 2013;Liu et al, 2020;Wang et al, 2021;Ikeda et al, 2022;Walther et al, 2022). The corticohippocampal network plays a critical role in cognition, especially memory: AT is mainly involved in recognition and associative memory, affective processing, semantic processing, and object perception (Diana et al, 2007), while PM is implicated in episodic and autobiographical memory for the context of an event, space and time, scene perception, and social cognition (Johnson and Rugg, 2007).…”
Section: Within-network Fc Abnormalities In Schsupporting
confidence: 91%
“…At the within-network level, we discovered decreased intrinsic FC in the cortico-hippocampal network, including the AT system, the PM system, and the anterior and posterior hippocampus, which is partially consistent with prior reports for schizophrenia (Benetti et al, 2009;Belujon et al, 2013;Liu et al, 2020;Wang et al, 2021;Ikeda et al, 2022;Walther et al, 2022). The corticohippocampal network plays a critical role in cognition, especially memory: AT is mainly involved in recognition and associative memory, affective processing, semantic processing, and object perception (Diana et al, 2007), while PM is implicated in episodic and autobiographical memory for the context of an event, space and time, scene perception, and social cognition (Johnson and Rugg, 2007).…”
Section: Within-network Fc Abnormalities In Schsupporting
confidence: 91%
“…The parasubiculum is also associated with the integration of information procession between hippocampus and cortex. The structural connections between the hippocampus and cortical/subcortical areas relates to cognitive impairment have been found in SZ but not in MDD (74,75). Two recent studies reported a volume reduction in parasubiculum in patients with MDD compared to HC, which correlated with plasma BDNF levels (76,77).…”
Section: Discussionmentioning
confidence: 99%